Associations between nighttime or weekend deliveries and adverse maternal, birth, and neonatal outcomes: secondary analysis of the MANGO study in western Kenya - Maneet K. Virk; Jenine Shafi; Pooja Maheria; Garoma Basha; Harold E. Kooreman; John Humphrey; James G. Carlucci; Audrey Chepkemoi; Caitlin Bernard; Megan S. McHenry; Beverly Musick; Caroline Kerich; et al. (BMC Pregnancy and Childbirth)
Abstract Background Maternal and neonatal morbidity and mortality remain high in low-income and middle- income countries (LMICs), and staffing schedules may contribute to adverse pregnancy outcomes. Particularly, during the nighttime and on weekends, provider staffing is often limited, which may make it difficult for pregnant persons to receive quality care. We leveraged existing data collected in a pharmacovigilance pregnancy project, named Measuring Adverse Pregnancy and Newborn Congenital Outcomes (MANGO) study, to determine any associations between nighttime/weekend deliveries and adverse (1) maternal, (2) birth, or (3) neonatal outcomes. Methods We conducted a secondary analysis of prospective data from the MANGO study, which documents delivery outcomes for pregnant persons at the Moi Teaching and Referral Hospital in western Kenya, from September 2020-November 2023. We utilized multivariable Poisson regression models, with log link, robust standard errors, and adjusted for several covariates, to assess the association between nighttime/weekend deliveries and adverse composite maternal, birth, or neonatal outcomes. Results A total of 25,911 neonates born to 25,247 pregnant persons were included. More than half of deliveries occurred during nighttime (6pm to 7am)/weekends (62.6%). In multivariate modeling, nighttime/weekend delivery was associated with a reduced risk of adverse composite maternal outcomes (adjusted risk ratio [aRR] 0.92, 95% confidence interval [CI]: 0.88, 0.96) and composite birth outcomes (aRR 0.92, 95% CI: 0.88, 0.96). No association was found between nighttime/weekend delivery and neonatal death. In post-hoc analyses, weekend deliveries were associated with reduced risk of emergency Caesarean deliveries, preterm birth, and low birth weight. Having advanced maternal age, obstetric complications, and transferring to the hospital for delivery were associated with adverse maternal and birth outcomes. Poor APGAR score was strongly associated with neonatal death. Conclusions Nighttime/weekend deliveries were associated with better maternal and birth outcomes, perhaps due to decreased emergency Caesarean deliveries for high-risk pregnancies or other factors. Greater attention to individual-level factors, such as obstetric complications, may be considered to improve outcomes for pregnant persons and their neonates. Future research may focus on under-resourced, non-tertiary hospitals to offer a more generalizable view of this exposure-outcome relationship in LMICs.